A study on syariah whipping as punishment for drugs dependants in Malaysia / Yuhanza Othman, Ida Rahayu Mahat and Ekmil Krisnawati Erlen Joni - Othman, Yuhanza; Mahat, Ida Rahayu; Erlen Joni, Ekmil Krisnawati (Division of Research and Industry Linkages, UiTM Melaka, 2014)
The government has introduced various programs to rehabilitate and give treatment to drug dependent. However statistic from Agency Anti Dadah Kebangsaan (AADK) has shown that a number of drug dependents has increased annually. It is high time for the government to review and enhance the punishment for drug dependents. The Drug Dependents (Treatment and Rehabilitation) Act 1983 is silent on imposing punishment on a first offender. Therefore, this paper will examines on imposing whipping as punishment for drug dependent as provided by syariah law. Adopting the application of qiyas, the rule and punishment of drinking liquor, which is stated in the Quran (5:90), and the Hadith is extended to consuming drugs. This paper seeks to discuss alternative methods to deter the public from drug abuse and at the same time to decrease the government expenditure in providing rehabilitation programs and services for drug (Abstract)